Effects of chronic exposure of specific water quality parameters in poultry drinking water on dietary amino acid digestibility and early broiler performance - Rabin Raut; Biswajit Kumar Biswas; Thyneice Taylor-Bowden; Agnes Kilonzo-Nthenge; Bharat Pokharel; Tom Tabler; Samuel N. Nahashon; Pramir Maharjan (Poultry Science)
Poultry drinking water quality parameters influence physiological functions and bird health. This study aimed to explore the impacts of poultry drinking water pH, TDS (total dissolved solids), and elevated levels of certain minerals on the early phase of broiler performance. Four treatment groups were created based on water source and water quality types: i) municipal water source (MW); ii) well/underground water source with moderately higher levels of Ca, SO4–, and Mn (WW); iii) high-pH (>8) water (HPH); and iv) high-TDS water (>3000 ppm) (HTDS). All treatment water samples were profiled for mineral content. Treatment water was fed ad libitum throughout the experimental period. A total of 288 birds (Cobb 500 males), fed a standard diet (day(d) 0-21), were utilized for the study, creating six replicates/treatment with 12 birds/replicate cage unit. Birds were weighed on days 0, 7, 14, and 21. Water consumption, body weight gain (BWG), feed consumption, feed conversion ratio (FCR), water: feed, and amino acid digestibility were measured. Statistical analysis was performed using 1-way ANOVA with Tukey's HSD test for significance (P < 0.05). Water consumption was higher for MW and HTDS until d10, but there was no difference in overall water consumption by d21 (P > 0.05). The overall feed intake and BWG were lower for HTDS birds compared to other treatment groups (P < 0.05), however, there was no difference in FCR (P > 0.05). Meanwhile, the apparent ileal digestibility of dietary amino acids for essential and non-essential amino acids did not differ among treatment groups (P > 0.05) and ranged from 0.40 to 0.94 across all treatments. The overall results showed that high-TDS water above 3000 ppm with elevated calcium and chloride levels could negatively impact early bird performance on feed consumption and BWG.